STRUCTURAL BEHAVIOUR OF STRENGTHENED HIGH PERFORMANCES CONCRETE – FILLED STEEL TUBE BEAMS - PARAMASIVAN, GOGHULAN (Universiti Teknologi PETRONAS, 2019)
Rapid development of Infrastructure is witnessed throughout the world. Many structures deteriorate that become unstable due to various reasons. Occurrence of natural calamities may also lead to one of the major problem. In many cases the past constructions reveal certain up gradations is necessary in three conditions which are the structure is inadequately designed for the loading conditions, structures that are found deficient under seismic conditions and the structure is damaged and requires rehabilitation. HPC has undergone many growths based on the persuade of cement type known as Ordinary Portland Cement (OPC) , type of mineral admixtures that are superplasticizer and the fine aggregates. The constituent materials of HPC depend on the desired characteristics and the availability of suitable local economic alternatives.